La mostra Fotografie astratte alla galleria L’Obelisco nel 1951: il sodalizio fra Pasquale De Antonis e Corrado Cagli - Schiaffini, Ilaria (Rivista di studi di fotografia. Journal of Studies in Photography, 2018)
This essay reconstructs the exhibition Fotografie astratte di De Antonis held at L’Obelisco Gallery in Rome in 1951. Focusing on the relationship between photographer Pasquale De Antonis and prominent painter and art critic Corrado Cagli, who wrote the catalogue essay, this study offers new insights about the nexus between abstract painting and photography in the cultural renaissance of post-WWII Italy. Close analysis of the Pasquale De Antonis Archive provides significant new information about his work. Special attention is devoted to the role played by L’Obelisco, at that time the most international and eclectic gallery in Rome.